Eligibility, Enrollment, and Completion of Exercise-Based Cardiac Rehabilitation Following Stroke Rehabilitation: What Are the Barriers?. Issue 1 (7th October 2019) - Marzolini, Susan; Fong, Karen; Jagroop, David; Neirinckx, Jennifer; Liu, Jean; Reyes, Rina; Grace, Sherry L; Oh, Paul; Colella, Tracey J F
Abstract: Background: People after stroke benefit from comprehensive secondary prevention programs including cardiac rehabilitation (CR), yet there is little understanding of eligibility for exercise and barriers to use. Objective: The aim of this study was to examine eligibility for CR; enrollment, adherence, and completion; and factors affecting use. Design: This was a prospective study of 116 consecutive people enrolled in a single outpatient stroke rehabilitation (OSR) program located in Toronto, Ontario, Canada. Methods: Questionnaires were completed by treating physical therapists for consecutive participants receiving OSR and included reasons for CR ineligibility, reasons for declining participation, demographics, and functional level. CR eligibility criteria included the ability to walk ≥100 m (no time restriction) and the ability to exercise at home independently or with assistance. People with or without hemiplegic gait were eligible for adapted or traditional CR, respectively. Logistic regression analyses were used to examine factors associated with use indicators. Results: Of 116 participants receiving OSR, 82 (70.7%) were eligible for CR; 2 became eligible later. Sixty (71.4%) enrolled in CR and 49 (81.7%) completed CR, attending 87.1% (SD = 16.6%) of prescribed sessions. The primary reasons for ineligibility included being nonambulatory or having poor ambulation (52.9%; 18/34 patients) and having severe cognitive deficits and no home exercise support (20.6%; 7/34). Frequently cited reasons for declining CR were moving or travel out of country (17.2%; 5/29 reasons), lack of interest (13.8%; 4/29), transportation issues (10.3%; 3/29), and desiring a break from therapy (10.3%; 3/29). In a multivariate analysis, people who declined CR were more likely to be women, have poorer attendance at OSR, and not diabetic. Compared with traditional CR, stroke-adapted CR resulted in superior attendance (66.1% [SD = 22.9%] vs 87.1% [SD = 16.6%], respectively) and completion (66.7% vs 89.7%, respectively). The primary reasons for dropping out were medical (45%) and moving (27%). Limitations: Generalizability to other programs is limited, and other, unmeasured factors may have affected outcomes. Conclusions: An OSR-CR partnership provided an effective continuum of care, with approximately 75% of eligible people participating and more than 80% completing. However, just over 1 of 4 eligible people declined participation; therefore, strategies should target lack of interest, transportation, women, and people without diabetes. An alternative program model is needed for people who have severe ambulatory or cognitive deficits and no home exercise support.